Realignment Expectations, Forward Rate Bias, and Sterilized Intervention in an Adjustable Peg Exchange Rate Model with Policy Optimization - Isard, Peter (IMF Working Papers; Working Paper ;, 1994)
The paper models an adjustable peg exchange rate arrangement as a policy rule with an escape clause under which the timing and magnitudes of realignments are the outcomes of policy optimization decisions. Under the assumptions that market participants are rational, risk averse, and fully informed about the incentives of policymakers, the analysis focuses on the implications for relating realignment expectations to the state variables that enter the policy objective function, for modeling the bias in using forward exchange rates to predict future spot rates, and for characterizing the effectiveness of sterilized intervention.